2004
DOI: 10.1093/jn/134.4.951
|View full text |Cite
|
Sign up to set email alerts
|

Food-Based Dietary Guidelines Can Be Developed and Tested Using Linear Programming Analysis

Abstract: Effective food-based dietary guidelines (FBDGs) are required to combat micronutrient deficiencies. This study aimed to develop a rigorous approach for designing population-specific FBDGs. A 4-phase approach based on linear programming analysis was used to design, test, and refine the FBDGs. This was illustrated for Malawian children. In phase I, the objective function minimized the difference in the energy contributed by different food groups between modeled and observed diets for 16 observed diet types, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 15 publications
0
86
0
Order By: Relevance
“…In contrast, most other studies using linear programming on diets focus on nutritional constraints exclusively [23,24,26,27,54], though some included cost successfully. The studies of Ferguson et al [23,54] for instance, were carried out to improve Food-Based Dietary Guidelines and Food Aid. Two studies, performed in France [55] and the USA [56], also looked at the costs and, for the nutritionally optimal diet, found both an increase in costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, most other studies using linear programming on diets focus on nutritional constraints exclusively [23,24,26,27,54], though some included cost successfully. The studies of Ferguson et al [23,54] for instance, were carried out to improve Food-Based Dietary Guidelines and Food Aid. Two studies, performed in France [55] and the USA [56], also looked at the costs and, for the nutritionally optimal diet, found both an increase in costs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in other countries-For instance the UK, France and New Zealand-Have successfully used linear programming for diet optimization [21][22][23][24][25][26][27][28][29]. Some of these studies demonstrated that cost constraints have a negative impact on nutritional values, and others showed that a healthy diet will not always have lower GHGE [30].…”
Section: Introductionmentioning
confidence: 99%
“…Linear programming for the optimization of local diets The LP method used is based on the work of Ferguson et al (21) . LP is a rigorous mathematical approach that optimizes (minimizes or maximizes) a linear function of a set of decision variables while meeting linear constraints.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Linear programming models optimize (minimize or maximize) linear functions of a set of decision variables, while respecting multiple linear constraints (Ferguson et al, 2003). A first step in developing a linear programming model for diet optimization is to establish a clear question that has to be addressed by the model.…”
Section: Model Formulation and Descriptionmentioning
confidence: 99%